Public discourse beyond the mainstream media: Intercultural conflict in socio-political discussion fora - Kleinke, Sonja; Avcu, Elif (Discourse, context & media, 2017)
Web 2.0 applications such as virtual online discussion fora have created a new form of public discourse beyond the mainstream media with new formats of public intercultural encounters, where the negotiation of intercultural conflicts is closely intertwined with the highly individualised and affective mutual- and self-construction of complex virtual cultural identities. In these fora, users often position themselves and their opinions in open opposition to broader cultural and social norms and contest mainstream media narratives, thereby also establishing an indirect link between public online and mainstream media discourse. Our study addresses two questions: Firstly, which linguistic strategies do participants use in order to construct themselves and others as members of a minority/majority culture and how do these constructed identities relate to mainstream media content? Secondly, how do participants position themselves vis-à-vis the mainstream media and what stances do they take towards mainstream media news coverage of long-term intercultural ethnic conflicts. To do so, we examine two threads from the public online discussion board UKDebate and one thread by the BBC-run Have your say, which deal with intercultural problems in the UK unfolding between UK-citizens and migrants and refugees from various cultural backgrounds. Our semantic analysis of users’ techniques of (self-)referencing and predication related to discourse topoi shows that participants use similar techniques when criticising mainstream media news-coverage and reception, but develop distinct group-specific patterns in shaping their respective cultural in- and out-groups. Furthermore, the discussions show similarities in the construction of minority groups between postings taking a majority perspective and tabloid news-coverage.
Gesehen am 29.10.2018